2020
DOI: 10.3390/w12041023
|View full text |Cite
|
Sign up to set email alerts
|

Tree-Based Modeling Methods to Predict Nitrate Exceedances in the Ogallala Aquifer in Texas

Abstract: The performance of four tree-based classification techniques-classification and regression trees (CART), multi-adaptive regression splines (MARS), random forests (RF) and gradient boosting trees (GBT) were compared against the commonly used logistic regression (LR) analysis to assess aquifer vulnerability in the Ogallala Aquifer of Texas. The results indicate that the tree-based models performed better than the logistic regression model, as they were able to locally refine nitrate exceedance probabilities. RF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 70 publications
(90 reference statements)
2
5
0
Order By: Relevance
“…Here, CART analysis of groundwater nitrate concentrations in small watersheds of Michigan's lower peninsula, a midwestern glacial landscape, identified aquifer recharge, SOC, agricultural nitrogen sources, and soil drainage properties (hydraulic conductivity) as key factors. This is generally consistent with other decision‐tree‐based studies throughout the United States that find variables related to sources, soil properties, and recharge as important factors (Burow et al., 2010; Messier et al., 2019; Pennino et al., 2020; Ransom et al., 2017; Tesoriero et al., 2017; Uddameri et al., 2020). Burow et al.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Here, CART analysis of groundwater nitrate concentrations in small watersheds of Michigan's lower peninsula, a midwestern glacial landscape, identified aquifer recharge, SOC, agricultural nitrogen sources, and soil drainage properties (hydraulic conductivity) as key factors. This is generally consistent with other decision‐tree‐based studies throughout the United States that find variables related to sources, soil properties, and recharge as important factors (Burow et al., 2010; Messier et al., 2019; Pennino et al., 2020; Ransom et al., 2017; Tesoriero et al., 2017; Uddameri et al., 2020). Burow et al.…”
Section: Discussionsupporting
confidence: 87%
“…Soil organic matter, a similar variable not quantified in this study, was also identified as an important variable correlated to agricultural activity and clay content by Uddameri et al. (2020).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although Noi et al [ 30 ] stated that Cubist regression and random forest algorithms have a good performance in estimating daily air surface temperature from dynamic combinations of MODIS LST data, Bayesian ANN notes to developing standard networks with posterior inference to regard a probability distribution of weights instead of a single set of weights [ 31 ]. Sahoo et al [ 32 ] put forward Bayesian methods for water quality assessment and presented that the quality of water was improved during dry seasons more than during wet seasons owing to the dilution of pollutants [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, random forest (RF) is an ensemble machine learning technique created by the fusion of bootstrapping aggregation and the algorithms of classification and regression trees (CART) [17]. RF is used in various fields, such as model prediction [16,18,19], attribute classification [20], and important feature selection [17,21]. The application of these machine learning tools to the large datasets of field-scale plants may be considered an efficient tool for performance evaluation and decision making.…”
Section: Introductionmentioning
confidence: 99%